Sexual Functioning in Young Adult Survivors of Childhood Cancer - Zebrack, Brad J. (2010)
BACKGROUND: Studies of sexuality or sexual behavior in childhood cancer survivors tend to examine relationships or achievement of developmental milestones but not physiological response to cancer or treatment. The purpose of this study is to (1) identify prevalence and risk factors for sexual dysfunction in childhood cancer survivors, and (2) examine the extent to which sexual dysfunction may be associated with health-related quality of life (HRQOL) and psychosocial outcomes. METHODS: Five hundred ninety-nine survivors age 18-39 years completed standardized measures of sexual functioning, HRQOL, psychological distress and life satisfaction. Descriptive statistics assessed prevalence of sexual symptoms. Bivariate analyses identified correlates of sexual symptoms and examined associations between symptoms and HRQOL/psychosocial outcomes. RESULTS: Most survivors appear to be doing well, although 52% of female survivors and 32% of male survivors reported at least “a little of a problem” in one or more areas of sexual functioning. Mean symptom score for females was more than twice that of males. Sexual symptoms were associated with reporting health problems. Significant associations between sexual functioning and HRQOL outcomes were observed, with gender differences in strengths of association suggesting that males find sexual symptoms more distressing than do females. CONCLUSIONS: While most survivors appear to be doing well in this important life domain, some young adult survivors report sexual concerns. While female survivors may report more sexual symptoms than male survivors, males may experience more distress associated with sexual difficulties. Better specified measures of sexual function, behavior and outcomes are needed for this young adult population.